2018
DOI: 10.1038/s41396-017-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Geobacteraceae are important members of mercury-methylating microbial communities of sediments impacted by waste water releases

Abstract: Microbial mercury (Hg) methylation in sediments can result in bioaccumulation of the neurotoxin methylmercury (MMHg) in aquatic food webs. Recently, the discovery of the gene hgcA, required for Hg methylation, revealed that the diversity of Hg methylators is much broader than previously thought. However, little is known about the identity of Hg-methylating microbial organisms and the environmental factors controlling their activity and distribution in lakes. Here, we combined high-throughput sequencing of 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 62 publications
0
74
0
Order By: Relevance
“…Altogether, our data suggest that microbial communities in anoxic ferruginous sediments exhibit vertical succession of the putative phenotypes FeRB, SRB, methanogens and methanotrophs (Fig. 5B), forming a microbial community different from those reported from lacustrine environments with ferruginous conditions in the pore water (Norði et al, 2013;Bravo et al, 2018). Although, the metabolic potential to reduce and disproportionate sulfur compounds was present, the absence of monosulfides and rapid increase of disulfides in the sediment suggested that cryptic sulfur cycling is minor, or even absent, compared to methanogenesis.…”
Section: Potential For Syntrophy and Methanogenesismentioning
confidence: 57%
“…Altogether, our data suggest that microbial communities in anoxic ferruginous sediments exhibit vertical succession of the putative phenotypes FeRB, SRB, methanogens and methanotrophs (Fig. 5B), forming a microbial community different from those reported from lacustrine environments with ferruginous conditions in the pore water (Norði et al, 2013;Bravo et al, 2018). Although, the metabolic potential to reduce and disproportionate sulfur compounds was present, the absence of monosulfides and rapid increase of disulfides in the sediment suggested that cryptic sulfur cycling is minor, or even absent, compared to methanogenesis.…”
Section: Potential For Syntrophy and Methanogenesismentioning
confidence: 57%
“…This 86 discovery has allowed for high-throughput identification of microorganisms with the 87 potential to methylate mercury in diverse environmental datasets based upon hgcAB 88 sequence presence (12, 13). 89Currently, the known diversity of mercury methylating microorganisms has been 90 described based on cultured isolates, amplicon sequencing of the 16S rRNA and/or hgcA 91 loci of mercury impacted sites, hgcA quantitative PCR (qPCR) primers targeting specific 92 5 groups, or identification of hgcA on assembled metagenomic contigs (11,(13)(14)(15)(16)(17)(18)(19)(20). 93 However, the complete phylogenetic and metabolic diversity of microorganisms capable 94 of methylating mercury is not fully understood due to previous efforts focusing on a few 95 cultured representatives, and poor predictive power of methylation potential based on 96 16S rRNA phylogenetic signal (8, 10, 21).…”
mentioning
confidence: 99%
“…Although the Hg could be methylated abiotically in the presence of suitable methyl donors (6), microorganisms are the prime agents responsible for Hg methylation (7)(8)(9). Recent studies using hgcAB (essential genes for Hg methylation) (10) as a biomarker have indicated that the potential for Hg methylation is spread much more broadly across more diverse microbial taxa than previously thought and includes the Deltaproteobacteria, Chloroflexi, Firmicutes, and Euryarchaeota (11)(12)(13)(14)(15). The produced MeHg may flow through food webs and accumulate in top predators through biomagnification (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The difference of Hg methylator assemblages between compartments within each site was also indicated by their diversity within a compartment (referred to as alpha diversity) and between compartments (referred to as beta diversity). The Chao1 richness estimator (an alpha diversity index) indicated that soil harbored the highest diversity of hgcAB OTUs (158 to 162), followed by floc (57 to 103), and periphyton (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) (Table S3). This tendency was in good agreement with the Shannon diversity indices, with 3.9 to 4.0 in soil, 3.0 to 3.1 in floc, and 2.1 to 2.8 in periphyton.…”
mentioning
confidence: 99%